Predictors of Need for Mechanical Ventilator Use in Critically Ill Surgical Patients - Phosri, Yoottapichai; Chayaput, Prangtip; Thosingha, Orapan; Srisuma, Sorachai (Journal of Thailand Nursing and Midwifery Council, 2021)
Objective: To examine the predictive power of surgery type, level of consciousness, principal diagnosis, and number of comorbidities to a need for mechanical ventilator use among critically ill surgical patients. Design: Retrospective predictive cross-sectional study Methodology: The samples were 111 patients who aged 18 years and over, received surgery under general anesthesia and admitted to Intensive Care Unit (ICU). Roy Adaptation Model was applied as a conceptual framework of the study. The researcher gathered retrospective data by reviewing patient’s medical records. The research instruments included demographic, clinical, and studied factors data record forms. Binary Logistic Regression with enter method was employed for predictive power analysis. Results: The samples had average age of 59.8 years (SD=17.4). 64.9% of them were males. It revealed that only surgery type and level of consciousness could significantly predict a need for mechanical ventilator use. Compared to patients received elective surgery, patients receiving emergency surgery had 2.94 times higher risk of the need for mechanical ventilator use longer than 48 hours (OR=2.939, 95%CI=1.002-8.621, p=.05). Patients with low level of consciousness (Glasgow coma score: GCS ≤ 8) had 4.77 times higher risk of the need for mechanical ventilator use longer than 48 hours compared to patients with high to moderate level of consciousness (GCS > 8) (OR=4.771, 95%CI=1.641-13.868, p<.01). The predictive model could explain the variance for 21.6% (Nagelkerke R2=.216). Recommendations: Critically ill surgical patients, who receive emergency surgery and have low level of consciousness (GCS ≤ 8), are more likely to report the need for mechanical ventilator use longer than 48 hours than any other groups. Their respiratory system might manifest ineffective response as an effort to maintain an equilibrium in oxygenation describing by Roy Adaptation Model. Critical care nurses should plan to assess these influential factors in order to provide nursing therapeutics that help promoting effective oxygenation adaptation, reduce the need for mechanical ventilator use, and prevent pulmonary complication in those groups of patients.